الصمود النفسي كمنبئ بالتدفق النفسي لدى المتفوقين دراسيا - غربي, منال; دحمري, أميرة (University of Eloued جامعة الوادي, 2023)
Abstract: The aim of the current study was to investigate psychological resilience as a predictor of academic flow among academically high-achieving students, given the importance of psychological resilience and academic flow in the academic field. The first hypothesis stated that there is a statistically significant relationship between levels of psychological resilience and levels of academic flow among high-achieving students. To test the hypotheses, a descriptive correlational method was adopted, and two instruments were used to collect the data: the Psychological Resilience Scale by researchers "Bacha Chaima Izzet" and "Imane Noussri Chenouda," and the Flow Scale by researchers "Al-Hadi Elseyed abdo " and "Farouk Elsayed Othmane." The study sample consisted of 90 academically high-achieving male and female students from some secondary schools in the province of Oued Souf. Regarding the statistical analysis, the Statistical Package for the Social Sciences (SPSS) was used. The correlation coefficient "Pearson," the "t-test" to determine the significance of differences, and the "simple linear regression analysis" to determine the predictive value were employed. The following results were obtained: • There is a statistically significant relationship between levels of psychological resilience and levels of academic flow among high-achieving students. • Academic flow can be predicted through psychological resilience among high-achieving students. • There are no statistically significant differences in the means of psychological resilience among high-achieving students based on gender. • There are statistically significant differences in the means of academic flow among high-achieving students based on gender. • There are no statistically significant differences in the means of psychological resilience among high-achieving students based on specialization. • There are no statistically significant differences in the means of academic flow among high-achieving students based on specialization. Keywords: psychological resilience, academic flow, high-achieving students. Résumé: L'objectif de l'étude actuelle était d'étudier la résilience psychologique en tant que prédicteur du flux académique chez les étudiants performants sur le plan académique, étant donné l'importance de la résilience psychologique et du flux académique dans le domaine universitaire. La première hypothèse affirmait qu'il existe une relation statistiquement significative entre les niveaux de résilience psychologique et les niveaux de flux académique chez les étudiants performants sur le plan académique. Pour tester les hypothèses, une méthode descriptive corrélationnelle a été adoptée, et deux instruments ont été utilisés pour collecter les données: l'échelle de résilience psychologique des chercheuses "Bacha Chaima Izzet" et "Imane Noussri Chenouda", et l'échelle de flux des chercheurs "Al-Hadi Elseyed abdo" et "Farouk Elsayed Othmane". L'échantillon d'étude était composé de 90 étudiants performants sur le plan académique, de sexe masculin et féminin, issus de quelques établissements secondaires de la province d'Oued Souf. En ce qui concerne l'analyse statistique, le logiciel "Statistical Package for the Social Sciences" (SPSS) a été utilisé. Le coefficient de corrélation "Pearson", le test "t" pour déterminer la signification des différences et l'analyse de régression linéaire simple pour déterminer la valeur prédictive ont été utilisés. Les résultats suivants ont été obtenus: • Il existe une relation statistiquement significative entre les niveaux de résilience psychologique et les niveaux de flux académique chez les étudiants performants sur le plan académique. • Le flux académique peut être prédit par la résilience psychologique chez les étudiants performants sur le plan académique. • Il n'y a pas de différences statistiquement significatives dans les moyennes de résilience psychologique entre les étudiants performants sur le plan académique en fonction du sexe. • Il existe des différences statistiquement significatives dans les moyennes de flux académique entre les étudiants performants sur le plan académique en fonction du sexe. • Il n'y a pas de différences statistiquement significatives dans les moyennes de résilience psychologique entre les étudiants performants sur le plan académique en fonction de la spécialisation. • Il n'y a pas de différences statistiquement significatives dans les moyennes de flux académique entre les étudiants performants sur le plan académique en fonction de la spécialisation.
دراسة ميدانية ببعض ثانويات ولاية الوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: الصمود النفسي، résilience psychologique, psychological resilience; التدفق النفسي، flux psychologique, psychological flow